'The fourth commandment effect': church attendance and intergenerational support in late parent–child relationships. Issue 1 (1st January 2020) - Tosi, Marco; Oncini, Filippo
ABSTRACT: We examine whether church attendance is related to intergenerational support from children to older parents in Italy. First, we focus on the role of church attendance on different forms of assistance, by distinguishing between practical support and personal assistance. Second, we attempt to disentangle the role of church attendance from that of traditionalism. We analyse data from the ISTAT survey 'Family and Social Subject' 2003 using multinomial logistic regression models and the KHB method for the decomposition of direct and indirect effects. Results show the existence of an association between church attendance and the probability of providing practical support to older parents, whereas there is no association with personal assistance. Regular churchgoers are more likely to provide practical support to their parents than the non-catholic, with occasional churchgoers falling somewhere in between. We find little support to the hypothesis that the association between religious practices and intergenerational support is explained by traditional family attitudes, although more traditional children are more likely to live with their parents. In the discussion, we argue that church attendance offers the opportunity for adult children to learn pro-family teachings that are positively related to supportive behaviors in later life.